Safety of VVER-440 reactors barriers against fission products release - Slugeén, Vladimair (Springer, 2011)
Safety of VVER-440 Reactors endeavours to promote an increase in the safety of VVER-440 nuclear reactors via the improvement of fission products limitation systems and the implementation of special non-destructive spectroscopic methods for materials testing. All theoretical and experimental studies performed the by author over the last 25 years have been undertaken with the aim of improving VVER-440 defence in depth, which is one of the most important principles for ensuring safety in nuclear power plants. Safety of VVER-440 Reactors is focused on the barrier system through which the safety principle is organised: nuclear fuel matrix; fuel cladding; integrity of primary circuit; and confinement system. All these barriers are described in detail and are compared to European standards. Industrial engineers will find Safety of VVER-440 Reactors a useful guide to the safe operation of nuclear power plants and it is an informative source of information for researchers in both industry and academia. Employees of related governmental and regulatory organisations may also benefit from reading this book